2005
DOI: 10.1002/pmic.200401022
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of alpha enolase in hepatitis?C virus-related hepatocellular carcinoma: Association with tumor progression as determined by proteomic analysis

Abstract: To identify proteins that could be molecular targets for diagnosis and treatment of hepatitis C virus-related hepatocellular carcinoma (HCV-related HCC), we used a proteomic approach to analyze protein expression in samples of human liver. Twenty-six pairs of tumorous and corresponding nontumorous liver samples from patients with HCV-related HCC and six normal liver samples were analyzed by two-dimensional gel electrophoresis and liquid chromatography-tandem mass spectrometry. One of the numerous spots that sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 24 publications
2
100
1
Order By: Relevance
“…[29][30][31] In addition, aenolase overexpression has been clinically associated with tumor status for lung and hepatocellular carcinoma. 32,33 a-Enolase induces an antibody response in almost two-third of PDAC patients, but not in healthy donors, non-PDAC tumor patients and chronic pancreatic patients. 18 PDAC patients did not display signs of autoimmunity, though the presence of anti-a-enolase antibodies has been described in patients with autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] In addition, aenolase overexpression has been clinically associated with tumor status for lung and hepatocellular carcinoma. 32,33 a-Enolase induces an antibody response in almost two-third of PDAC patients, but not in healthy donors, non-PDAC tumor patients and chronic pancreatic patients. 18 PDAC patients did not display signs of autoimmunity, though the presence of anti-a-enolase antibodies has been described in patients with autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…We found that MBP-1 may regulate tumor progression in gastric cancer through the MBP-1-COX-2 signaling axis. In addition to gastric cancer, MBP-1 was shown to participate in tumorigenesis of several tumors (Ray et al, 1995;Chang et al, 2003;Ejeskar et al, 2005;Ghosh et al, 2005a;Ghosh et al, 2005b;Takashima et al, 2005;Ghosh et al, 2006a;Ghosh et al, 2006b). Interestingly, COX-2 overexpression is observed in a variety of malignancies (Sano et al, 1995;Ristimäki et al, 1997;Hida et al, 1998;Zimmermann et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…MBP-1 and ␣-enolase are involved in tumorigenesis (Ray et al, 1995;Chang et al, 2003;Ejeskar et al, 2005;Ghosh et al, 2005a;Ghosh et al, 2005b;Takashima et al, 2005;Ghosh et al, 2006a;Ghosh et al, 2006b) and metastasis (Ray et al, 1995;Chang et al, 2003;Demir et al, 2005). It was proven that MBP-1 has the potential of a candidate for gene therapy against tumor growth (Chang et al, 2003;Ghosh et al, 2005b;Ghosh et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, clinical tissue samples have been the most extensively studied samples in HCC proteomic studies and most studies compared protein expression profiles between tumor tissue and adjacent non-tumor tissue Lim et al, 2002;Takashima et al, 2003Takashima et al, , 2005Yokoyama et al, 2004;Zeindl-Eberhart et al, 2004;Li et al, 2005). One study compared the protein profiles among HBV þ , HCV þ and HBVÀ/ HCVÀ HCC tumor tissues using 2D-PAGE-MS and found that among the 60 differentially expressed proteins when comparing tumor and non-tumor tissues, 46 proteins were specific to the underlying viral etiology (Kim et al, 2003).…”
Section: Tumor Tissuesmentioning
confidence: 99%